Giant first-forbidden resonances - Krmpotić, F.; Nakayama, K.; Galeão, A.Pio [UNESP] (Elsevier, 1983)
Recent experimental data on first-forbidden charge-exchange resonances are discussed in the framework of a schematic model. We also evaluate the screening of the weak coupling constants induced by both the giant resonances and the Δ-isobar. It is shown that the last effect does not depend on the multipolarity of the one-particle moment. Due to the same reason, the fraction of the reaction strength pushed up into the Δ-resonance region is always the same regardless of the quantum numbers carried by the excitation. Simple expressions are derived for the dependence of the excitation energies of the first-forbidden giant resonances on the mass number and isospin of the target. The model reproduces consistently both the Gamow-Teller and the first-forbidden resonances. © 1983.